"The Only Option Is Failure": Growing Safe to Fail Workplaces for Critical Reflection. Issue 3 (August 2020) - Nicolaides, Aliki; Poell, Rob F.
The Problem: Whereas critical reflection has been the hallmark of learning from experience in the workplace, performance has been the hallmark for productivity. In the face of complex, ongoing, disruptive change, failing safe is a necessary condition for learning from experience, and critical reflection the method of learning from safe to fail experiments. How can workplaces be safe to fail spaces where critical reflection is embraced, encouraged, and rewarded? The Solution: We focus especially on the role of the leader to create a climate of psychological safety where it is safe to practice critical reflection. The workplace needs to become a safe place to fail to facilitate productivity, innovation, and creative responses to the demands that ensue from disruption at work. The Stakeholders: This article is relevant to human resource development (HRD) scholars and practitioners who are interested in developing the workplace in times of uncertainly and constant disruption.